1990
DOI: 10.1111/j.1469-8137.1990.tb00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon flow into soil and external hyphae from roots of mycorrhizal cucumber plants

Abstract: summary Cucumber (Cucumis sativus L.) plants grown in PVC tubes with a partially sterilized soil‐sand mixture were inoculated with the vesicular‐arbuscular mycorrhizal fungus Glomus fasciculatum (Thaxter) Gerdemann & Trappe emend. Walker & Koske or left uninoculated. The soil column of each PVC tube was divided into a root and a hyphal compartment by a mesh bag (60 μm), which retained the roots but allowed external hyphae to pass. Inoculated plants rapidly became infected and an extensive mycelium developed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
258
2
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 505 publications
(274 citation statements)
references
References 28 publications
11
258
2
3
Order By: Relevance
“…In the latter study, Gange & West (1994) found that mycorrhizal Plantago lanceolata had lower levels of total N than did plants in which colonization was experimentalK' reduced, and other reports also suggest that AM colonization can tower soluble N levels (Trimble & Knowles, 1995). Mycorrhizal fungi are a considerable carbon drain on a host, w ith 10-20 " o of annual photosynthate being directed to the fungus (Jakobsen & Rosendahl, 1990) and this, coupled with the lowering of plant N concentration, could have serious consequences for a gall-forming insect which does not have the abilit>' to move and seek alternative food sources. However, such problems may be tempered by the abilirv' of the adult female to discriminate between suitable and unsuitable plants (Fernandes & Price, 1991).…”
mentioning
confidence: 87%
“…In the latter study, Gange & West (1994) found that mycorrhizal Plantago lanceolata had lower levels of total N than did plants in which colonization was experimentalK' reduced, and other reports also suggest that AM colonization can tower soluble N levels (Trimble & Knowles, 1995). Mycorrhizal fungi are a considerable carbon drain on a host, w ith 10-20 " o of annual photosynthate being directed to the fungus (Jakobsen & Rosendahl, 1990) and this, coupled with the lowering of plant N concentration, could have serious consequences for a gall-forming insect which does not have the abilit>' to move and seek alternative food sources. However, such problems may be tempered by the abilirv' of the adult female to discriminate between suitable and unsuitable plants (Fernandes & Price, 1991).…”
mentioning
confidence: 87%
“…Colonisation of roots by AMF can alter plant C allocation (Jakobsen and Rosendahl 1990) (depending on developmental stage Mortimer et al 2005), and stimulate plant photosynthetic rates (Smith and Read 1997). Allocation of C to AMF may vary with stage of plant development (Mortimer et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon flow to the roots is known to be increased when hosts are mycorrhizal due to the sink activity of the fungal endophyte (Jakobsen & Rosendahl, 1990). Rhinanthus spp.…”
Section: mentioning
confidence: 99%